2017
DOI: 10.1002/uog.18934
|View full text |Cite
|
Sign up to set email alerts
|

Gonadotropin‐releasing hormone agonists for ovarian protection during cancer chemotherapy: systematic review and meta‐analysis

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
38
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(50 citation statements)
references
References 56 publications
2
38
0
2
Order By: Relevance
“…However, notably, the trials were not designed nor powered to assess differences in post-treatment pregnancies, pregnancy desire was not a criteria for study inclusion and most of the trials reported results at a short follow-up time without the possibility of assessing this important outcome. Although the numbers remain low, all the most recent meta-analyses reported a significantly higher number of post-treatment pregnancies in breast cancer patients who received GnRHa during chemotherapy as compared to those treated with systemic cytotoxic therapy alone [114,115,117,118,120], with no benefit in lymphoma patients [118].…”
Section: Critical Appraisal Of the Available Clinical Evidencementioning
confidence: 99%
See 1 more Smart Citation
“…However, notably, the trials were not designed nor powered to assess differences in post-treatment pregnancies, pregnancy desire was not a criteria for study inclusion and most of the trials reported results at a short follow-up time without the possibility of assessing this important outcome. Although the numbers remain low, all the most recent meta-analyses reported a significantly higher number of post-treatment pregnancies in breast cancer patients who received GnRHa during chemotherapy as compared to those treated with systemic cytotoxic therapy alone [114,115,117,118,120], with no benefit in lymphoma patients [118].…”
Section: Critical Appraisal Of the Available Clinical Evidencementioning
confidence: 99%
“…Several meta-analyses have been conducted to summarize the results from the available randomized trials performed to investigate the clinical efficacy of temporary ovarian suppression with GnRHa during chemotherapy in premenopausal cancer patients (Table 6) [101][102][103][104][105][106][107][108][109][110][111][112][113][114][115][116][117][118][119][120]. The oldest meta-analyses included also prospective non-randomized studies, some were restricted to a single tumor type (i.e.…”
Section: Meta-analyses Of Randomized Trialsmentioning
confidence: 99%
“…Adult literature has had mixed results on the efficacy GnRH agonists for gonadal protection and prevention of ovarian failure . A recent systematic review and meta‐analysis found that GnRH agonists had a benefit in patients with breast cancer, but not for lymphoma patients . Given that providers indicate that a primary reason for using GnRH agonists was potential gonadal protection, there are limited data that this will be protective in AYAs with cancer, additional provider education regarding the use of GnRH agonists may be beneficial.…”
Section: Discussionmentioning
confidence: 99%
“…[36][37][38][39][40] A recent systematic review and meta-analysis found that GnRH agonists had a benefit in patients with breast cancer, but not for lymphoma patients. 41 Given that providers indicate that a primary reason for using GnRH agonists was potential gonadal protection, there are limited data that this will be protective in AYAs with cancer, additional provider education regarding the use of GnRH agonists may be beneficial. Additionally, investigation should be done to better understand how providers counsel patients regarding GnRH agonists as well at patients' perceptions of GnRH utilization and gonadal protection.…”
Section: Patient Factors Related To Menstrual Suppressionmentioning
confidence: 99%
“…В связи с этим важным является вопрос о сохранении овариального резерва после цитостатической терапии. В клинической практике существует такая возможность, для этого используются гонадотропинрилизинг-гормоны, уменьшающие количество клеток мишеней (делящихся клеток) путем остановки функции яичников [8]. Однако это только одна сторона решения проблемы, которая стоит в тесной связи с другой -необходимостью снижения риска генетических нарушений, вызываемых цитостатиками в созревающих ооцитах.…”
Section: Introductionunclassified